Aragonite and calcite preservation in sediments from Lake Iznik related to bottom lake oxygenation and water column depth. Issue 7 (22nd October 2016) - Roeser, Patricia; Franz, Sven O.; Litt, Thomas
Abstract: This study examines the forcing mechanisms driving long‐term carbonate accumulation and preservation in lacustrine sediments in Lake Iznik (north‐western Turkey) since the last glacial. Currently, carbonates precipitate during summer from the alkaline water column, and the sediments preserve aragonite and calcite. Based on X‐ray diffraction data, carbonate accumulation has changed significantly and striking reversals in the abundance of the two carbonate polymorphs have occurred on a decadal time scale, during the last 31 ka calbp . Different lines of evidence, such as grain size, organic matter and redox sensitive elements, indicate that reversals in carbonate polymorph abundance arise due to physical changes in the lacustrine setting, for example, water column depth and lake mixing. The aragonite concentrations are remarkably sensitive to climate, and exhibit millennial‐scale oscillations. Extending observations from modern lakes, the Iznik record shows that the aerobic decomposition of organic matter and sulphate reduction are also substantial factors in carbonate preservation over long time periods. Lower lake levels favour aragonite precipitation from supersaturated waters. Prolonged periods of stratification and, consequently, enhanced sulphate reduction favour aragonite preservation. In contrast, prolonged or repeated exposure of the sediment–water interface to oxygen results in in situ aerobic organic matter decomposition, eventually leading to carbonate dissolution. Notably, the Iznik sediment profile raises the hypothesis that different states of lacustrine mixing lead to selective preservation of different carbonate polymorphs. Thus, a change in the entire lake water chemistry is not strictly necessary to favour the preservation of one polymorph over another. Therefore, this investigation is a novel contribution to the carbon cycle in lacustrine systems.